Evaluation of a Low-Cost Strategy for Enumerating CD4 Lymphocyte Absolute Count and Percentage Using the FACSCalibur Flow Cytometer in HIV-Infected Patients from a Resource-Limited Setting. (23rd October 2012) - Alvarez-Uria, Gerardo; Reddy, Raghuprakash; Reddy, Srinivasulu; Naik, Praveen K.; Midde, Manoranjan
Abstract : Enumeration of CD4 lymphocytes is essential for the clinical management of HIV-infected patients, but it can be difficult to afford in developing countries. In this study we evaluated a reagent reduction strategy for reducing the cost of enumerating CD4 cell absolute count and percentage using the FACSCalibur flow cytometer (Becton Dickinson). We compared the protocol recommended by the manufacturer with a protocol that used half of the usual amount of CD3/CD4/CD45 monoclonal antibody reagent in 100 samples from HIV-infected patients in a rural hospital in India. The concordance correlation coefficient between the two protocols was 0.976 for CD4 cell count and 0.984 for CD4 cell percentage. We did not find significant bias when performing Deming regression or Bland-Altman analysis. Sensitivity and specificity were 97% and 98.5% for identifying patients with less than 200 CD4 cells/ μ L, 98.1% and 93.8% for identifying patients with less than 350 CD4 cells/ μ L, and 100% and 94.7% for identifying patients with less than 25% CD4 cells, respectively. This reagent reduction strategy can be used for reducing the cost of enumerating CD4 lymphocytes in high-volume laboratories from resource-limited settings.